SmartFarm monitoring and evaluation framework and strategy white paper - Faulkner L (WorldFish, 2013)
The WorldFish Bangladesh’s SmartFarm action research project has to date taken a logical framework approach to Monitoring and Evaluation (M&E). In line with the original project logframe, SmartFarm aims to contribute towards the overall objective that “a range of climate smart aquatic agricultural interventions in four villages in Bangladesh are widely adopted.” The purpose is to identify, test, evaluate and promote climate change risk management and adaptation practices at household and community level in order to create “farms of the future” that implement optimized integrated farming systems. This is to ensure that present and future farming communities that possess low adaptive capacity and live in the climate vulnerable south-western Bangladeshi districts of Satkhira, Bagerhat and Jhalokhati, are better able to meet their income and food production requirements in light of local changing dynamic contexts of climate risk.